Pricing Mechanism for Collateral Auctions in Problematic Financing at Bank Syariah Indonesia, Palangka Raya - Sofyan Hakim; Hanief Monady; Nadia Safitri (At-Taradhi Jurnal Studi Ekonomi, 2022)
A Sharia bank is an institution whose main business is to provide credit and other services based on sharia principles. A sharia bank has various products, one of which is financing. However, risks in financial institutions are inevitable and become potential events, both foreseeable and unpredictable. Such as financing customers who end up experiencing defaults and leading to the sale of collateral or collateral through auctions. Therefore, it is necessary to know the mechanism for pricing collateral auctions and constraints on problematic financing at Sharia Bank of Indonesia, Palangka Raya City. This research uses a descriptive qualitative approach. The results of this study are that the pricing mechanism is carried out with the provisions and procedures applicable at Sharia Bank of Indonesia, Palangka Raya City, with price interpretation carried out by the assessment team after the survey is carried out, looking for appeal data based on the prevailing market value in the collateral area, looking at collateral conditions, interpreting until finally the price is determined based on the applicable mechanism in accordance with the Circular Letter of the Board of Directors must use the price reference Central Market, Regional Market Price, and Local Market Price. Pricing carriess out with appropriate assessments and calculations based on the market approach method and cost approach that have been formulated to be used as a guide in the assessment and pricing of collateral auctions in accordance with the fair price or market price that occurred at that time.